â€œSmile pleaseâ€ or â€œyouâ€™re being watchedâ€ impact of CCTV notices on consumer responses in service scapes - V.U, Vinitha; S, Anoop (International Journal of Engineering and Technology, 2018)
Security systems are imperative for businesses in every service contexts. Closed Circuit Television (CCTV) is one of the ways to ensure commercial security for business. Although such systems are said to protect against potential theft or customer misbehavior, they can influ-ence the productivity levels of employees as well as attitude and purchase intention of customers in servicescapes. The paper studies the influence of CCTV notices on attitude and purchase intention of customers in two different service contexts: utilitarian and hedonic. Positive and negative toned messages, identified through a pilot test, were used in an experimental design. The results indicate that the attitude and purchase intention of the customers are high when they are exposed to positive toned CCTV notices as against negative toned CCTV notic-es. The study further reveals that the purchase intention of the female customers is higher than the male customers when they were exposed to the positive CCTV notice. However, no evidence was found to support any difference between the impacts of message tones in the two service environment contexts.Â Â